2022
DOI: 10.3390/cosmetics9060136
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging, Anti-Acne, and Cytotoxic Activities of Houttuynia cordata Extracts and Phytochemicals Analysis by LC-MS/MS

Abstract: Although many biological properties of Houttuynia cordata have been found, its anti-aging and anti-acne effects have not yet been investigated. This study was aimed to evaluate the in vitro anti-aging and anti-acne activities of H. cordata extracts and their cytotoxic activities and phytochemicals analyzed with liquid chromatography with tandem mass spectrometry (LC-MS/MS). Dried aerial parts of H. cordata were given different extractions. The aqueous and ethanolic extracts obtained were named HCA and HCE, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Quercetin significantly reduces cholesterol levels [33,34], where cholesterol is a component of sebum [35]. The results were consistent with reports that the extract works well for acne-prone skin while gently controlling the sebum [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Quercetin significantly reduces cholesterol levels [33,34], where cholesterol is a component of sebum [35]. The results were consistent with reports that the extract works well for acne-prone skin while gently controlling the sebum [9].…”
Section: Discussionsupporting
confidence: 90%
“…Phenolic compounds from HCE, such as alkaloids and flavonoids (hyperoside, afzelin, and quercetin) are beneficial as active ingredients for cosmetics [4,6,7]. Moreover, many studies have found that HCE contains compounds with antioxidant properties [8], antibacterial properties (strong anti-microbial effects against the bacteria most commonly contributing to acne: Propionibacterium acnes and Staphylococcus epidermidis) [9], antiviral activity [10][11][12], anti-inflammatory properties [13,14], anti-skin-aging properties [15,16] and anti-allergic effects [15,17]. Some…”
Section: Introductionmentioning
confidence: 99%
“…Most antibacterial activity studies have been performed on Bacillus sp., E. coli , and Staphylococcus aureus [ 40 , 41 ]. Notably, in 2022, a study by Phosri et al (2022) investigated the antibacterial activity of H. cordata using aqueous and ethanol extraction methods [ 16 ]. The MIC values against the C. acnes strain for the aqueous and ethanol extracts were 5.77 mg/mL and 2.47 mg/mL, respectively, significantly higher than the values obtained in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rutin H. cordata was proven to effectively prevent UV-induced damages associated with proinflammatory and prooxidative activity and protect cells against apoptosis [ 15 ]. H. cordata extract has been studied for potential anti-aging and anti-acne properties without attempting to detect immune cell and skin properties [ 16 ]. These have become significant advantages in the cosmetics and beauty industry.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical composition of the selected Thai herbal extracts was determined by LC-MS/MS analysis as the previous study [34]. Briefly, the samples of extracts (500 ppm) were prepared by dilution in the absolute methanol and then filtered through a 0.2 μm NYL filter, and filled into a vial.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%